Figurative Language in Emily Dickinson’s Selected Poems - Girsang, Martina; Pasaribu, Junro; Sinaga, Elisabeth Pratiwi Norico; Ginting, Khalia Milfani Br; Nazara, Yoana (eScience Humanity Journal, 2023)
The aims of this study is to analysis and describe the types of figurative language found in Emily Dickinson’s selected poems. Figurative language deviates from conventional usage by emphasizing changes in the word order or syntactical structure rather than the meaning of the words themselves. Figurative language can be defined as a language style that poets and other artists employ to create literary works of art in an effort to make the language more beautiful. According to Gorys Keraf figurative language is how and the way of expressing thought through language in the unique way that shows the soul and the personality of the author. The theory used in this paper is the theory of Gorys Keraf. The source of the data in this paper include the line , verse, and the stanza of 4 poems from Emily Dickinson entitled Hope Is The Things With The Feather, A Bird Come Down The Walk, I Heard A Fly Buzz When I Died, and I’m Nobody! Who Are You . This paper uses a descriptive qualitative method. The figure of speech found in this paper is metaphor, hyperbole, personification, and simile, allusion, synecdoche, alliteration.